Touristic events as generators of visitations increase and tourism sustainability of nature parks in continental Croatia? - Jankovic, Bozodar; Tubić, Dejan; Bakan, Rikard (Turizam, 2018)
The protected areas of nature in the 21st century record continuous growth, since they can satisfy diverse desires, needs and expectations of contemporary and extremely fragmented tourist demand. However, level of visit greatly depend on the category, resource attractiveness, additional supply and other authentic features of the protected area. According to that, in some of the recently established nature parks, tourism still does not sufficiently contribute to the economic sustainability of their own park agencies, and even less to the local community. Although long-term financial independence of park agencies and the survival of nature parks is questionable, currently there is no clear interest in Croatia in exploring this field. The main purpose of this paper is to determine to what extent tourist events can contribute to increasing recognisability, level of visit and the economic sustainability of nature parks. For this purpose, the research was carried out on all five Public institutions of nature parks (PINPs) in continental Croatia. Primary data was conducted by a semi-structured interview. An essential feature of these five nature parks is that they are far from the major receptive mass tourism destinations, which differentiates them from those who are significantly more receptive due to these circumstances. Research findings suggest that touristic events, which are a significant factor in seasonality reduction, bring a multiple benefit for nature parks such as increasing level of visit, recognisability, image creation etc. However, they do not contribute to the economic sustainability of nature parks due to their unprofitability. In addition to events, the results indicate that nature parks should develop other, accompanying tourist attractions and facilities considering their lower rank of protection.